Sustainable urban planning. Vibrant neighbourhoods, smart cities, resilience. 2nd ed. - (:unkn) unknown (Ed. Detail, 2019)
Life in the city is popular and creating liveable urban space is undoubtedly a priority for planners. Yet what makes a city worth living in? How do we define sustainable neighbourhoods that will function properly and continue to attract people in the future? What does "Smart City" or "resilience" really mean? The completely revised, new edition of this publication provides the answers. It addresses the fundamental challenges of urban planning today and offers planners essential knowledge, implementation strategies and ways toward holistic concept development. Examples of international neighbourhood developments clearly show how aspects of sustainable urban planning can be implemented in practice.
Keywords: Stadtplanung; Smart City; Nachhaltige Entwicklung; Resilienz; Stadtquartier; Quartiersentwicklung; Nachbarschaft; Partizipation; Stadtökologie; Planungsinstrument; Implementation; Fallstudie; Lebensqualität; Urbanität; Local Governance